Short-selling restrictions, strategic stock holdings and index futures markets in Finland - Pekka Hietala; Esa Jokivuolle; Yrjö Koskinen (Bank of Finland, 1994)
The goal of the paper is to rationalize the observed persistent underpricing in the Finnish stock index futures market.It is shown that under a binding short-selling restriction on stocks the observed futures "underpricing" can be a result of strategic motives of the Finnish industrial and financial groups to hold large amounts of stocks, which implies a net futures demand for hedging part of the financial risk brought in by these strategic holdings."Underpricing" can also emerge under short-selling restrictions, if strategic investors are better informed than other traders.Two main empirical implications of the model - a negative relationship between the futures basis and stock index volatility and a positive relationship between the basis and private information signals received by informed investors - are supported by the Finnish data from May 1988 to December 1990.
URN:NBN:fi:bof-20140807587
Keywords: 330